The theatricality of accountability: The operation of governing bodies in schools. (July 2017) - Farrell, Catherine; Morris, Jonathan; Ranson, Stewart
The shift from political leadership to new forms of governance has led to the establishment of locally appointed bodies in many public organizations including schools. From a dramaturgical perspective, this article focuses on the accountability of these new bodies, in particular on the codes of accountability. Using school governing bodies to illustrate, the article evaluates whether accountability in practice might be likened to a theatrical performance. The findings presented are relevant to school governing bodies and there may be wider application in public sector boards more generally.